ECONOMY DEVELOPMENT: BENCHLEARNING - Malobabic, Vanja (Journal of Economic Development, Environment and People, 2012)
Benchlearning like new method integrates efficient methods and human development at a time when such integration is recognized as increasingly vital to organizational succes. It: -offers practical inspiration on improving quantitative goals -company performance and competitiveness-by influencing the attitudes of people within the organization -provides a new method combining the qualities of both the learning organization and knowledge management -shows how this concept can be applied using case studies and illustrations and the result of pilot project -describes practical perspectives and tools on management and learning theory. This work will be invaluable to senior and middle managers, consultants and practitioners and MBA students, as well all those working within organizations that are keen to improve and develop their performance. The aim is to produce a business strategy which will make organizations work more efficiently. Different aspects of ‘ the economics of learning’ have been the main content research. This work answers the question ’how do you know that your operation is efficient?’Benchlearning show that it is possible to move on from pure comparison to benefit from the knowledge and experience of others and create a real learning organization. Examples from a range of organizations including Ericsson show how to monitor efficiency, provide inspiration for a development drive, and illustrate how to influence people’s experience, in combination with the principles of organizational learning. Benchlearning principles can be applied to almost any group or company to promote a win-win-win situation: employees’ performance improves as they learn to develop, customers gain more value and choice, and owners benefit from a more competitive organization.